Analisis Determinan Non-Performing Financing pada PT Bank Jabar Banten Syariah Tbk. - Dirgawanti, Nikita Triyuli; Barnas, Benny; Hadiani, Fatmi; Ruhana, Nafisah (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
The amount of Non-Performing Financing is thought to be caused by the influence of internal and external factors in the Islamic banking industry, including Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), Account Receivable Turnover (ARTO), Inflation, and Gross Regional Domestic Product (GRDP). The data used in this study was soourced from the quarterly financial statements of PT. Bank Jabar Banten Syariah for the period 2014-2021. The analysis methods used are multiple liear regression, classical assumption testing, and hypothesis testing. From this study, it was obtained that CAR and FDR did not affect NPF, ARTO had a significant positive effect on NPF, Inflation had a significant positive effect on NPF, and GRDP had a significant positive effect on NPF. Simultaneously, CAR, FDR, ARTO, Inflation and GRDP have a significant influenct on Non-Performing Financing.